2020
DOI: 10.1159/000506439
|View full text |Cite
|
Sign up to set email alerts
|

Chemically Soluble Fluoride in Na<sub>2</sub>FPO<sub>3</sub>/CaCO<sub>3</sub>-Based Toothpaste as an Indicator of Fluoride Bioavailability in Saliva during and after Toothbrushing

Abstract: The relationship between the concentration of chemically soluble fluoride found in toothpaste and that present in saliva, during and after brushing, was evaluated as an indicator of potentially bioavailable fluoride in toothpaste. Ten adult participants brushed their teeth with the assigned toothpastes: group I: fresh sample of a fluoride toothpaste: Na 2 F-PO 3 /CaCO 3 , 1,378 µg F/g of total soluble fluoride (TSF); groups II-IV: aged samples of toothpaste presenting TSF concentrations of 1,160, 900, and 597 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 32 publications
2
14
0
5
Order By: Relevance
“…Furthermore, our data showed that fluoride was found in a chemically soluble form in all the mouth rinses evaluated. Unlike toothpaste, 22 all fluoride in mouth rinses is potentially bioavailable when released in the oral cavity during rinsing. Nevertheless, it is known that some substances, such as detergents used in mouthwash formulations, may interfere with the effect of fluoride.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our data showed that fluoride was found in a chemically soluble form in all the mouth rinses evaluated. Unlike toothpaste, 22 all fluoride in mouth rinses is potentially bioavailable when released in the oral cavity during rinsing. Nevertheless, it is known that some substances, such as detergents used in mouthwash formulations, may interfere with the effect of fluoride.…”
Section: Discussionmentioning
confidence: 99%
“…Em seguida, lavaram a boca com água purificada e as amostras foram novamente colhidas. Amostras de saliva não estimuladas foram coletadas antes e após a escovação em diferentes intervalos de tempo (3,6,9,15,30,45, 60 e 120 minutos), concluindo-se que o fluoreto capaz de se manter biodisponível na saliva para exercer ação anticárie é o flúor solúvel. Além disso, após a etapa de envelhecimento das amostras, para obter diferentes concentrações de flúor para análise, o valor do flúor total encontrado não sofreu alteração em nenhum momento 6 .…”
Section: Discussionunclassified
“…O uso do creme dental fluoretado é considerado o método mais racional de uso do fluoreto, uma vez que, em conjunto com a escovação, promove a desorganização do biofilme, ao mesmo tempo em que expõe as superfícies dentárias ao íon flúor, o qual se mantém presente no biofilme remanescente pós-escovação não eficiente e na saliva e, desta forma, mantém o equilíbrio desmineralização-remineralização tecidual. O fluoreto liberado na cavidade bucal serve tanto como efeito preventivo, para reduzir o desenvolvimento de lesões de cárie, quanto como efeito terapêutico, agindo na reparação das lesões iniciais já existentes [6][7][8][9] .…”
Section: Introductionunclassified
See 1 more Smart Citation
“…The protocol of fluoride determination in toothpastes with F-ISE by the direct technique and used since 1980 in Laboratory of Oral Biochemistry from FOP-UNICAMP 3,5,7-20 is considered chemically valid, reliable, and feasible 1 . In addition, it is able to estimate how much of the total fluoride presents in Na 2 FPO 3 /CaCO 3 -based toothpaste is bioavailable to be released in the oral cavity during toothbrushing 21 . However, this protocol could be simplified to determine fluoride in Ca-free toothpaste formulations, which contains ionic fluoride salts, such as NaF.…”
Section: Discussionmentioning
confidence: 99%